2013
DOI: 10.1210/me.2012-1247
|View full text |Cite
|
Sign up to set email alerts
|

Induction of 11β-HSD 1 and Activation of Distinct Mineralocorticoid Receptor- and Glucocorticoid Receptor-Dependent Gene Networks in Decidualizing Human Endometrial Stromal Cells

Abstract: The actions of glucocorticoids at the feto-maternal interface are not well understood. Here, we show that decidualization of human endometrial stromal cells (HESCs) in response to progesterone and cAMP signaling is associated with a strong induction of 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) expression and enzyme activity. Decidualization also triggered a gradual decrease in glucocorticoid receptor (GR) expression and reciprocal increase in mineralocorticoid receptor (MR) levels. Gene expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 60 publications
2
68
0
Order By: Relevance
“…PGR knockout female mice exhibited similar deficiencies accompanied by implantation defects and the absence of ESC decidualization after progesterone stimulation [32, 36]. Moreover, whether other steroid hormones such as testosterone, mineralocorticoids or glucocorticoids are involved, is warranted given its role in decidualization [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…PGR knockout female mice exhibited similar deficiencies accompanied by implantation defects and the absence of ESC decidualization after progesterone stimulation [32, 36]. Moreover, whether other steroid hormones such as testosterone, mineralocorticoids or glucocorticoids are involved, is warranted given its role in decidualization [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Perturbed or inadequate decidualization leads to embryo miscarriage and early pregnancy failure (Kommagani et al 2013). Accompanied by typical morphological changes, differentiating stromal cells express biochemical decidual markers, such as prolactin (PRL), insulin-like growth factor-binding protein-1 (IGFBP1) (Irwin et al 1994, Brar et al 1997) and 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) (Brosens et al 1999, Kuroda et al 2013. Data from Ozaki et al (2017) showed that RARs, as well as CRABP2 and FABP5, which are responsible for binding and delivering RA to nuclear receptors RARs and PPARβ/δ respectively, decreased in decidualizing human endometrial stromal cells despite an increase in PPARβ/δ.…”
Section: Stromal Decidualizationmentioning
confidence: 99%
“…RA plays fundamental roles in the normal maintenance of endometrial physiology (Zheng et al 2000, Sidell et al 2002, Ding et al 2003, Kuroda et al 2013, and aberrant RA metabolism might be a predisposing factor for the development of endometriosis (Pavone et al 2011, Wieser et al 2012, Pierzchalski et al 2014, Yamagata et al 2015. However, a comprehensive and systematic analysis and understanding of RA pathway in endometrial physiology and pathology remain lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the activity of steroid hormones in the uterus is primarily mediated by the uterine microenvironment. Stromal and immune cells present in the uterine milieu regulate angiogenesis and vascular remodeling (Kuroda et al 2013). Many pro-angiogenic and anti-angiogenic modulators are expressed in the endometrium (Becker et al 2006, Saǧsöz andSaruhan 2011).…”
Section: Physiological and Pathological Angiogenesis In The Uterusmentioning
confidence: 99%